Genetics of primary congenital glaucoma - Atif Amin, Baig; Muhammad Umer, Khan; Wajeeha, Tabassum (2019)
Primary Congenital Glaucoma (PCG) is a major risk factor for vision loss in children, which is manifested from birth to three years of age. In PCG the ocular developmental defects of the trabecular meshwork (TM) and front chamber position of eye lead to the blockage of aqueous loss and consequently an increased intraocular pressure (IOP). This results in photophobia, corneal clouding, optic nerve damage, and ultimately permanent loss of vision occurs. The incidence of PCG varies geographically. In Eastern culture, consanguineous marriages may play a role in a higher rate of PCG. Four loci of GLC3A, GLC3B, GLC3C, and 14q24.2-q24.3 to be linked to this ocular condition have been identified. Currently, mutations in two genes i.e.CYP1B1 at GLC3A locus, which encodes cytochrome P4501B1, and LTBP2 at GLC3D locus, which encodes LTBP2is known to cause PCG.CYP1B1 comprises of 3 exons encoding a 543 amino acid protein. CYPIBI is a gene that belongs to the cytochrome P450 family of enzymes. The cytochrome P450 proteins are monooxygenases that catalyse many reactions involved in the synthesis of cholesterol, steroids, other lipids, and drug metabolism. A lot of mutations have been reported in CYP1B1, which results in the form of PCG.